Credit Market Development and Firm Innovation: Evidence from China - Hội thảo quốc tế Ngân hàng và Tài chính thế giới 2015 (Trường Đại học Kinh tế, 2020)
From the perspective of credit allocation, this paper analyzes the effect of credit market development on firms’ innovative capacities in China. Using a large data set of Chinese industrial firms in 31 provinces, we find out that, from the credit allocation perspective, credit market development enhances both firms’ innovation incentives and outcomes. We show that firms’ credit constraints and firms’ performances are two channels through which the credit market development affects firms’ innovative capacities. The innovation incentives and outcomes of more credit restrained firms and firms with better performances are affected by credit market development more than those of other firms. In addition, we demonstrate that our results are not driven by the increase of the number of firms